DEVELOPMENT OF PHONETIC COMPETENCES OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS - Jabbarova Lobar (Journals Park Publishing, 2022)
The article examines how English-speaking elementary school students develop their phonemic awareness. The discrepancy between pupils' actual levels of knowledge and the school's expectations for their phonetic knowledge and skills is the issue raised in this study. It examines the theoretical approaches and methods for instructing younger students in the phonetics of a foreign language.
Keywords: speech activity, speech characteristics, pronunciation